PERBANDINGAN HASIL TANGKAPAN UTAMA DAN SAMPINGAN ALAT TANGKAP TRAWL PADA MALAM HARI DI PERAIRAN SAMBOJA KUALA KABUPATEN KUTAI KARTANEGARA - Ahmad Fauzi; Muhammad R. Syahrir; Nurfadilah Nurfadilah (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2022)
As an area bordering the Makassar Strait, Samboja Kuala District, most of the people make a living as fishermen. The fishing gear used by fishermen to catch shrimp and fish is a trawl. This study aims to identify the types of catches, determine the comparison of the percentage of main and by-catch at night. The method used in this study is a survey method, namely by going directly to the field. The main catches were 8 species of shrimp, namely Penaeus monodon, Penaeus sp, Penaeus merguiensis, Metapenaus affinis, Metapenaus monoceros, Metapenaeopsis palmenis, Metapenaeopsis barbata and Solenocera crassicornis. While the by-catch there are species of fish, cuttlefish and squid. The percentage of the main catch that was dominantly caught was Metapenaus affinis at 61% and the smallest was Penaeus sp 0%. While the percentage of by-catch is the most dominant fish beloso 33% and the smallest is grouper and bigeye fish 1% with a significance value <0.05 (sig. 0.24). The results of this study can show that there are differences in the main catch and by-catch in trawl fishing gear at night.